Utilizing CO2 as a strategy to scale up direct air capture may face fewer short-term barriers than directly storing CO2 - Brazzola, Nicoletta; Moretti, Christian; Sievert, Katrin; Patt, Anthony; Lilliestam, Johan (Environmental Research Letters, 2024)
Direct air capture (DAC) is increasingly recognized as a necessary puzzle piece to achieve the Paris climate targets. However, the current high cost and energy intensity of DAC act as a barrier. Short-term strategies for initial deployment, technology improvement, and cost reduction are needed to enable large-scale deployment. We assess and compare two near-term pathways leading to the same installed DAC capacity and thus yielding the same cost reductions: its combination with CO2 storage as direct air carbon capture and storage, or its deployment for CO2 utilization as direct air carbon capture and utilization e.g. for synthetic fuels, chemicals, and materials; we characterize these as Direct and Spillover pathways. Drawing on the Multi-level Perspective on Technological Transition as a heuristic, we examine both technical and immaterial factors needed to scale up DAC under the two pathways, in order to assess the pathways’ relative advantages and to identify possible short-term bottlenecks. We find neither pathway to be clearly better: the Direct pathway offers technical advantages but faces regulatory barriers that need to be resolved before deployment, while the Spillover pathway offers market and governance advantages but faces challenges related to hydrogen production and increasing resource needs as it scales up. There may be reasons for policymakers to therefore pursue both approaches in a dynamic manner. This could involve prioritizing the Spillover pathway in the short term due to possibly fewer short-term regulatory barriers and its ability to produce net-zero emission products for existing and accessible markets. Once short-term governance obstacles have been addressed, however, the Direct pathway may allow for more efficient scaling of DAC capacity and cost reductions, especially if by then the needed infrastructure and institutions are in place.
CRIS-Team Scopus Importer:2024-05-03
Keywords: carbon removal; CO; DACCS; DACCU; direct air capture; socio-technical systems; technology development pathways